Atividade antibacteriana, antioxidante e citotóxica in vitro do extrato etanólico da entrecasca da planta Ouratea hexasperma (EEEOH) (A. St-Hil.) Baill var. Planchonii Engl - COSTA, Glauber Vilhena da (Universidade Federal do Pará, 2017)
Ouratea hexasperma (Ochnacea), popularly known as "cerrado barbatimão" is a very common plant in the brazilian cerrado region and has been used for the treatment of microbial infections and inflammation. Therefore, this study aimed to evaluate the antioxidant activities, quantifying total flavonoid content (TFT), antibacterial and cytotoxicity of ethanol extract of the bark of Ouratea hexasperma (EEBOH) as well as perform their phytochemical characterization. The plant was collected in the state of Amapá, and then was held extraction of dry bark through the cold maceration with 96% ethanol solution in a 2: 8 (w/v) for 1 day, forming the EEBOH. The phytochemical characterization was performed by testing chromatic/precipitation tube and flavonoid content was measured by assay complexation with aluminum using quercetin as standard (40-0,62μg/mL), and the total antioxidant capacity by the spectrophotometric method discoloration radical ABTS•+ (2,2'azino-bis-3-etilbenzotiazolin 6-sulfonic acid) - TEAC. The antimicrobial activity of EEBOH was tested against gram-positive and gram-negative bacteria, using the microdilution techniques broth with staining by resazurin, to determine the Minimum Inhibitory Concentration (MIC), and grown in petri dish with subsequent count of colony forming units (CFU) for obtaining the Minimum Bactericidal Concentration (MBC). The evaluation of the cytotoxicity of EEEOH human peripheral blood leukocytes. Mononuclear peripheral blood cells incubated with different concentrations of the extract and without stimulation (negative control). The cytotoxicity of EEEOH were tested using human peripheral blood leukocyte, mononuclear cells, with different extract concentrations and without stimulation (negative control), and incubated and maintained at 37 ° C, 98% humidity and 5% CO2 for 24 hours, NO and MDA were read in an ELISA spectrophotometer and different optical readings. The primary EEBOH phytochemical analysis showed the presence of tannins, saponins and flavonoids. The TFT in the extract was 1467 ± 264μg equivalents quercetin/g EEBOH. The antioxidant capacity by TEAC method showed high antioxidant activity, with no difference in antioxidant capacity (TEAC) between those concentrations of the extract. The EEBOH showed good antibacterial activity, mainly against gram-positive bacteria. The cytotoxicity was obtained by linear regression concentration able to kill 50% of cells (CC 50%) whose amount was 2231,5mg/mL, confirming that the crude extract has low cytotoxicity against human leukocytes, under the conditions tested. In the production of NO and MDA it found that the EEOC was not able to induce NO production of the concentrations tested. As well, no increase MDA of concentration induces changes when compared to the negative control (RPMI), confirming the low in vitro cytotoxicity of the extract. Statistical analyzes were performed by ANOVA one way and Turkey. In concluded that the EEBOH have antibacterial, antioxidant and low cytotoxicity.